Опыт преподавания ГИС-технологий в Томском политехническом университете - Ананьев Ю. С. Юрий Сергеевич; Житков В. Г. Владимир Георгиевич; Поцелуев А. А. Анатолий Алексеевич; Орехов А. Н. Александр Николаевич (2005, 2005)
В фонде НТБ ТПУ отсутствует